2017
DOI: 10.14744/anatoljcardiol.2016.7149
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum adropin level and burden of coronary artery disease in patients with non-ST elevation myocardial infarction

Abstract: Objective:Previous studies revealed the relationship between stable coronary artery disease (CAD) and serum adropin level, but this relationship has not been investigated in patients with non-ST segment elevation myocardial infarction (NSTEMI). The present study is an analysis of the relationship between adropin and severity of CAD assessed based on SYNTAX score in patients with NSTEMI.Methods:A total of 109 participants, 80 patients with NSTEMI and 29 healthy individuals, were prospectively enrolled in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…These studies were screened layer by layer. Finally, there were seven studies included (8)(9)(10)(11)(12)(13)(14). The literature screening process and results are shown in Figure 1.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies were screened layer by layer. Finally, there were seven studies included (8)(9)(10)(11)(12)(13)(14). The literature screening process and results are shown in Figure 1.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…We are the first meta-analysis of the relationship between adropin and CAD so far in the world. A total of 7 casecontrol studies were included in this meta-analysis (8)(9)(10)(11)(12)(13)(14), including 525 CAD patients and 420 healthy controls. The results of meta-analysis showed that the levels of serum adropin in patients with CAD, AMI, UAP and SAP were significantly lower than those in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies indicate that adropin influences cardiovascular system function and participates in the pathogenesis of several cardiovascular diseases ( Lovren et al, 2010 ; Topuz et al, 2013 ; Wu et al, 2014 ; Gu et al, 2015 ; Zhao et al, 2015 , 2016 ; Gulen et al, 2016 ; Ertem et al, 2017 ; Oruc et al, 2017 ; Bolayır et al, 2018 ; Sato et al, 2018 ; Altamimi et al, 2019 ; Thapa et al, 2019b ). Firstly, adropin determines the condition of the endothelial cells (EC).…”
Section: Adropinmentioning
confidence: 99%
“…Ertem A. G. et al on a group of patients with NSTEMI carried out the investigation, showed adropin's link with atherosclerosis. It resulted in a state that adropin plays a role in development of atherosclerotic burden in NSTEMI patients (14). Therewith, Çelik et al (15) demonstrated that lower serum adropin levels are associated with cardiac syndrome X (CSX).…”
Section: Table 3 Spearmen Rank Order Correlation Between Cimt and Otmentioning
confidence: 99%